Arianne Conty, "Grounding God: Religious Responses to the Anthropocene" (2023) - Macallan, B. (Journal for the academic study of religion, 2025)
Arianne Conty, Grounding God: Religious Responses to the Anthropocene, New York: SUNY Press, 2023, pp. 211, AUS $ 43.00, ISBN 9781438495743 (pbk).